Lower versus standard intensity oral anticoagulant therapy (OAT) in elderly warfarin-experienced patients with non-valvular atrial fibrillation - Pengo, Vittorio; Cucchini, Umberto; Denas, Gentian; Davidson, Bruce L.; Marzot, Filippo; Jose, Seena Padayattil; Iliceto, Sabino (Thrombosis and Haemostasis, 2010)
It has been observed that elderly patients with nonvalvular atrial fibrillation (NVAF) benefit from standard [an international normalised ratio (INR) goal of 2.0–3.0] oral anticoagulant treatment (OAT). The hypothesis that lower-intensity anticoagulation therapy can offset the higher bleeding risk in this population has never been tested in an ‘ad hoc’ clinical trial. Patients over 75 years of age with NVAF were randomised to receive warfarin to maintain the INR at 1.8 (range 1.5–2.0) or at a standard target of 2.5 (range 2.0–3.0). There were 135 patients in the low-intensity and 132 in the standard-intensity groups. During a mean follow-up lasting 5.1 years, 59 primary outcome events (thromboembolism and major haemorrhage) were recorded, 24 (3.5 per 100 patient-years) in the low-intensity group and 35 (5.0 per 100 patient-years) in the standard-intensity group (HR=0.7, 95% CI 0.4–1.1, p=0.1). The reduction in the primary endpoint was mainly due to a diminution in major bleedings (1.9 vs. 3.0 per 100 patient-years; HR=0.6, 95% CI 0.3–1.2, p=0.1). The median achieved INR value was 1.86 in the low-intensity and 2.24 in the standard-intensity group (p<0.001). The frequency of INR testing was 26.1 ± 13.5 vs. 24.3 ± 11.6 days, p<0.0001). In this exploratory study we observed a low rate of stroke and major bleeding in elderly patients (>75) being managed in an anticoagulation clinic for primary stroke prevention with low-intensity anticoagulation (INR 1.5–2.0). However, further trials are needed to confirm the hypothesis generated by the present study.
Keywords: Clinical trials; oral anticoagulants; stroke; prevention; thrombosis